PENILAIAN FORM GERITATRIC DEPRESSION SCALE (GDS) PADA LANSIA DENGAN HIPERTENSI DI WILAYAH KERJA PUSKESMAS TAMIANG LAYANG - Dewi Purnama Sari; Rian Tasalim (LPPM STIKes Mitra Adiguna, 2024)
Depression and hypertension are common conditions that often occur in the elderly and can influence each other. Depression assessment using the Geriatric Depression Scale (GDS) in elderly people with hypertension at the Tamiang Layang Community Health Center is important to improve quality of life and prevent more serious health complications. This study aims to determine the assessment of the GDS form in elderly people with hypertension. This research uses a quantitative descriptive design with a cross-sectional approach. The research sample was 30 elderly people with hypertension who were taken by purposive sampling. Data was collected using the GDS questionnaire and analyzed descriptively. Of the 30 elderly people studied, 17 (56.67%) were men and 13 (43.33%) were women. A total of 10 (33.33%) respondents had grade 1 hypertension and 20 (66.67%) had grade 2 hypertension. The level of depression was found to be in the normal category in 8 (26.67%) respondents, mild depression in 19 (63.33%) %) respondents, and moderate-severe depression in 2 (6.67%) respondents. The research results showed that the majority of elderly people with hypertension experienced mild depression. Depression in elderly people with hypertension can worsen their physical health condition and reduce their quality of life. Therefore, the use of GDS as a routine screening tool in Community Health Centers is very important for detecting and managing depression early. Depression assessment using GDS in elderly with hypertension at the Tamiang Layang Community Health Center showed a high prevalence of mild depression. Implementation of routine screening and early intervention is needed to improve the quality of life of the elderly.